2015
DOI: 10.2217/fmb.15.63
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis and Function of Porphyromonas Gingivalis Outer Membrane Vesicles

Abstract: Porphyromonas gingivalis is one of the keystone pathogens associated with chronic periodontitis. All P. gingivalis strains examined thus far produce outer membrane vesicles. Recent studies have found that vesicles possess some well-known virulence factors of P. gingivalis such as adhesins, toxins and proteolytic enzymes. Carrying most of the characteristic features of their parent P. gingivalis cells, vesicles communicate with host cells and other members of microbial biofilms, resulting in the transmission of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 80 publications
2
60
0
Order By: Relevance
“…[14][15][16][17] Porphyromonas gingivalis possesses a vast array of effector molecules and systems that enables its colonization and survival in the oral cavity, communication with other bacteria and, ultimately, virulence. [18][19][20][21] Two distinct fimbriae composed of FimA and Mfa1, respectively, are the most well-documented virulence factors of P gingivalis. 22 Fimbriae contribute to colonization, biofilm formation, cell invasion, bone resorption, and the evasion of the host defense systems.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Porphyromonas gingivalis possesses a vast array of effector molecules and systems that enables its colonization and survival in the oral cavity, communication with other bacteria and, ultimately, virulence. [18][19][20][21] Two distinct fimbriae composed of FimA and Mfa1, respectively, are the most well-documented virulence factors of P gingivalis. 22 Fimbriae contribute to colonization, biofilm formation, cell invasion, bone resorption, and the evasion of the host defense systems.…”
Section: Introductionmentioning
confidence: 99%
“…P. gingivalis vesicles originate from outer membrane blebbing and contain mostly outer membrane components including lipopolysaccharides and outer membrane proteins (Xie, 2015) and exhibit the primary features of this organism. In fact, we recently demonstrated that P. gingivalis vesicles exhibit much higher invasive efficiency than their originating bacterial cells, although it appears that both invasive processes involve a clathrin-mediated endocytic machinery (Ho et al, 2015, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Gram-negative organisms, including known oral pathobionts, have been shown to play important roles in interspecies interaction and to contain factors that trigger an inflammatory response (37,38).…”
mentioning
confidence: 99%